Analisis Perubahan Garis di Kawasan Pesisir Kabupaten Asahan Provinsi Sumatera Tahun 2015-2020 - Marbun, Sahala Fransiskus; Simarmata, Gomoses; Saputri, Dwi Aulia; Saragih, Cahyani; Gultom, Qania (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Coastal change is a common phenomenon in various coastal areas around the world. This phenomenon can be caused by natural factors such as waves, ocean currents, tides, and climate change, which lead to rising sea levels. In addition, human activities such as coastal land conversion, infrastructure development, and exploitation of natural resources can also drive coastal change. These changes can occur in the form of damage, which can cause reduction or accumulation, and increase land area due to sedimentation. The impact of these changes not only threatens coastal ecosystems, but also affects the lives of people who rely on coastal livelihoods. Asahan Regency, located on the east coast of North Sumatra, is one of the areas where the coastline has undergone significant changes. Various factors, both natural and human-induced, contribute to the dynamics of the coast in the region.